ChemInform Abstract: An (Aminopyrimidinato)titanium Catalyst for the Hydroamination of Alkynes and Alkenes. Issue 23 (10th June 2014) - Brahms, Christian; Tholen, Patrik; Saak, Wolfgang; Doye, Sven
Abstract An efficient catalyst for intermolecular hydroamination of alkynes and intramolecular hydroamination of alkenes [e.g. (XIV)] is presented.